(untitled) (Biological Sciences - PJSIR, 2000)
Using ISTA techniques, the seed-borne mycoflora of cucumber (Cucumis sativus L.) was studied. The blotter method was found to be the most suitable technique for detection offungi in cucumber seed. Deep freezing method was preferable for the detection of Fusarium spp. A total of 18genera and 33 species were isolated, of which 25 have not hitherto been recorded from seeds of cucumber in Pakistan.